O equilíbrio entre o elemento irracional e racional na ideia de sagrado em Rudolf Otto - Santos, Edson Kretle dos (2012)
The purpose of this dissertation is to elucidate in what way the rational and the irrational elements frame the human notion of the sacred, according to the philosopher Rudolf Otto. Marked by XX Century s rule of reason, Otto reacts to the Enlightenment, which interprets the sacred solely as metaphysical, moral and evolutional formulations. After the Kantian critique, the knowledge path becomes an impossible way to the understanding of the sacred and of the religious phenomenon. Thus, the author recaptures the sentiment as the origin and the openness of the human search for the divine. Since the experience of the nouminous belongs to the sphere of the sentiment, it follows that it is understood, constituted and characterized by the irrational aspect, for the religious experience has the peculiarity of the mysterious. Given this argument, Otto responds to the Enlightenment Age stating that the mystery of the sacred shall never be encompassed by reason alone. On the other hand, a religion based exclusively on sentiment contributes to the emergence of various self-denominated miraculous, magical religious practices. The theological reflections of such religions tend to mix capitalist exchanges and divine promises of prosperity. Otto reveals himself as a supremely important philosopher in the analysis of many contemporary religious practices which emphasize the emotional aspect. In such religions the exclusion of reason is evident, which the author rejects as inconceivable, given the argument that the rational element is a fundamental component of religion. Hence, Otto s intention, as well as that of this dissertation, is to demonstrate that the religious experience is composed both by the irrational and the rational elements and that only when these two aspects are in a state of healthy balance it is possible to achieve a profound experience of the divine.